Peningkatan Produktivitas Kerja Melalui Rotasi Jabatan Studi Kasus: The Jayakarta Suite Hotel and Resort Bandung - Thia Kharin Fauziah Sunarya; Vany Octaviany (Syntax Literate, 2023)
The productivity of employees at The Jayakarta Suite Hotel & Resort Bandung has experienced a decline, necessitating a job rotation to enhance work productivity. This study aims to explore work productivity and job rotation, as well as the role of job rotation in improving work productivity at The Jayakarta Suite Hotel & Resort Bandung, particularly in the F&B Service department. This research employs a qualitative ethnographic approach. Data collection techniques involve interviews, observations, and documentation of HRD, F&B managers/supervisors, and F&B employees at The Jayakarta Suite Hotel & Resort Bandung. The findings of this research indicate that job rotation has positive effects on the company and employee career progression, yet its implementation has not proven effective in boosting work productivity. Older employees, being the majority, feel comfortable in their current positions and show no interest in job rotation. Efforts to enhance work productivity can be accomplished through skills upgrading, job evaluations, and focusing on physical factors.